Spatial Analysis of Breeding Places of Anopheles sp. Mosquitoes as Potential Vectors of Malaria Infection in Pesawaran District, Lampung, Indonesia - Athma, Dwi Aji; Suwandi, Jhons Fatriayadi; Mayaguezz, Henky; Setyaningrum, Endah; SRW, Dyah Wulan; Darmawan, Arief (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2025)
Malaria is an infectious disease caused by microorganisms of the genus Plasmodium, transmitted to humans by the female Anopheles mosquito species. The breeding place of this Anopheles mosquito is typically found in the environment, such as stagnant water in rivers, abandoned ponds, lagoons, and other similar areas. Pesawaran Regency is a malaria-endemic area in Lampung Province with an API of 1.4 in 2023. Mapping the distribution of breeding places is necessary to control malaria vectors in Pesawaran Regency. Based on this, this study will conduct a spatial analysis of the breeding sites of Anopheles sp. mosquitoes, which are potential vectors of malaria infection in Pesawaran District. This type of research is descriptive observational using cross sectional design, coordinate survey and visual inspection of larvae found in breading place and spatially processed using Arcgis V.10.8. From the observations of breeding places in the form of swamps, water reservoirs (buckets and derigen) unused fish ponds or ponds, buffering breeding place analysis carried out can be seen that malaria cases are in the area of vector flight distance of 1,000 meters and 3,000 meters. Potential breeding places were found in Teluk Pandan sub-district of Pesawaran Regency, breeding places are scattered in five villages and are located in coastal areas with a distance between 407.88 meters - 707.266 meters from the coastline, buffering analysis of breeding places can be seen that the location at risk of malaria case transmission is in the vector flight distance area of 1,000 meters and 3,000 meters covering eight villages.